S14-2 Signaal: online tool for reporting and assessment of new occupational health risks. (1st September 2016) - Lenderink, Annet F
Abstract : Changes in work and working conditions may give rise to new occupational health risks. Despite efforts to detect and reduce these risks, it is plausible that new occupational hazards may occasionally introduce new work-related diseases. A specifically designed online reporting system, tested in an occupational health setting in the Netherlands and Belgium, can provide valuable data on possible new and emerging occupational health risks by creating a structured way to report and assess new combinations of health problems and exposure in the work place.